Stability of a dynamical system with semi-Markov switchings under conditions of diffusion approximation - Chabanyuk, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We obtain sufficient conditions for the stability of a dynamical system in a semi-Markov medium under the conditions of diffusion approximation by using asymptotic properties of the compensation operator for a semi-Markov process and properties of the Lyapunov function for an averaged system.